Body image and Self-Objectification in a Confucian Cultural Context: Self-Representation and Consumption of Desirable Feet on Douyin (TikTok) in China - Zhang, Xiaolong (KOME, 2024)
While issues related to gender and mental health have been extensively discussed in the context of body image based on objectification theory, there has been limited exploration of the interplay between gender, sexual attention, and self-representations in online communication, particularly concerning specific body parts within a given cultural context. Podophilia, the most common sexual fetish, includes a range of interests in feet, such as foot tickling, kissing, foot jobs, and shoe/stocking play. Traditionally, these activities have been linked to offline experiences. However, in the digital age, particularly in China, where the government is committed to prohibiting erotic and sexually explicit materials, content displaying various private body parts faces restrictions under Chinese media and internet policies. Interestingly, the representation of feet and legs remain relatively unrestricted, resulting in a significant amount of sexually suggestive media content related to these body parts. This study aims to investigate the influence of culture, policy, and economics on self-representations of foot and leg related content and the consumption of such content in the Chinese online environment. Through the analysis of 500 Douyin videos and 5000 corresponding online comments, this research disclosed how video creators portray their body parts, why these videos are predominantly women-centered, and why these women are more or less self-objectified.